A Thorough Systematic Review Of The Prevalence, Risk Factors, Management, And Outcome Of Preeclampsia In Pregnancy - Afifah; Ayu, Aulia (The Indonesian Journal of General Medicine, 2024)
Background: Preeclampsia is a hypertension-related condition that is associated with a number of risk factors, such as race and ethnicity, as well as a history of hypertension. Aspirin prophylaxis and prenatal counseling can help lower the risk, but infections, high blood pressure, ovarian syndrome, and breathing disorders during sleep can all raise it as well. Methods: This systematic review, following PRISMA 2020 guidelines, analyzed full-text English literature published between 2014 and 2024, excluding editorials and review articles from submissions without a DOI, using websites like ScienceDirect, PubMed, and SagePub. Result: After a thorough three-step screening process, eight papers were determined to have pertinent connections to our current in-depth investigation. Following that, the entire text was closely scrutinized, and additional attention was paid to these specific passages. Conclusion: Preeclampsia increases pregnancy complications, maternal illnesses, and hypertension in some regions. Preventive measures include lifestyle modifications, tertiary prevention, and aspirin prophylaxis. Prenatal management strategies include magnesium sulfate infusions and corticosteroids.